Salvage endovascular embolization of the left pulmonary artery for recurrent pseudoaneurysm - Yojiro Yutaka; Junichi Tasaki; Itsuki Yuasa; Kotaro Murakami; Hiroshi Date (Surgical Case Reports, 2021)
Abstract Background Pulmonary pseudoaneurysm (PPA) is a potentially lethal complication of lung resection with a high risk of recurrence after endovascular coiling. Case presentation We report a case in which recurrent hemoptysis due to PPA after left lower lobe sleeve resection was treated by endovascular embolization of the left main pulmonary artery as a salvage treatment. The first hemoptysis was managed by endovascular coil embolization with extracorporeal membrane oxygenation, but refractory hemorrhage occurred 3 months later due to penetration of the endovascular coil into the bronchial anastomosis site. Because left completion pneumonectomy was considered too high risk, the left main pulmonary artery was palliatively embolized using an Amplatzer vascular plug (St. Jude Medical, MN, USA) to totally disrupt the left pulmonary arterial flow. Conclusions Total embolization of the left main pulmonary artery for repeated PPA rupture may be useful as a palliative treatment in patients unable to tolerate pneumonectomy.